An Application For Semantic Annotation Of Web Services - Budinoski, Koste; Jovanovik, Milosh; Stojanov, Riste; Trajanov, Dimitar (Institute of Informatics, Skopje, Macedonia, 2010)
The progress in the field of web services has made it possible to publish, locate, and invoke specific applications across the Web. This is the reason why more and more companies and organizations now implement their core business, or outsource other application services, over the Internet. Therefore, the efficient selection and integration of inter-organizational services on the Web, at runtime, becomes an important issue to the web service provision. The general question is how to develop mechanisms to automatically locate the correct web service in order to meet the user's needs. In special cases, if no single web service can satisfy the functionality required by the user, there should be a possibility to combine existing web services together, in order to fulfil the request. In this paper, we present a web application that uses ontologies in order to semantically annotate web services, in order to enable the necessary processes, such as automatic discovery, automatic invocation and automatic composition of semantic web services [1]. The application uses the SAWSDL mechanism [2] to connect the concepts of semantic models from an ontology, with the WSDL [3] components. Its main aim is to provide an easy and flexible user interface, presenting the web service description as a tree structure, and allowing the addition of ontologies that would be used for annotation. All of the web services are stored into a one central public repository, which would later be used for automatic web service discovery, automatic invocation and automatic composition.
Keywords: Semantic web services, Annotation, Ontologies, Applications